Mass drug administration for neglected tropical disease control and elimination: a systematic review of ethical reasons - Sabine Salloch; Juliette Hoefle-Bénard (BMJ Global Health)
Background Neglected tropical diseases (NTDs) are a diverse group of debilitating diseases and conditions afflicting more than one billion people in impoverished communities. Control of these diseases is crucial to achieve Sustainable Development Goal 3 and the pledge to ‘leave no one behind’. Relying on large-scale delivery of wide-spectrum drugs to individuals in at-risk communities irrespective of their health status, mass drug administration is a core strategy for tackling half of the NTDs targeted by the latest WHO roadmap (2021–2030). However, ethical challenges surround its implementation and long-term impact. This systematic review aims to give a comprehensive picture of the variety of ethical reasons for and against mass drug administration for NTD control and elimination, facilitating further debate in ethics and policy.Methods PubMed and Web of Science Core Collection were searched for all relevant publications. Of the 486 retrieved records, 60 met the inclusion criteria for qualitative analysis. Ethical reasons discussing the topic at hand were extracted from full texts and synthesised through the Kuckartz method of qualitative content analysis.Results Data extraction revealed 61 ethical reasons, of which 20 (32.7%) had positive, 13 (21.3%) had ambivalent and 28 (45.9%) had negative implications regarding mass drug administration for NTDs. The health benefits and cost-effectiveness of the measure were extensively highlighted. However, equity, autonomy and sustainability emerged as the domains with the most pressing ethical concerns. Many issues related to implementation are yet to be adequately addressed in policy documents.Conclusions This is the first systematic review of ethical reasons pertaining to mass drug administration for NTD control and elimination. Due to the diversity of included studies, no general recommendations can be made. Instead, context-specific strategies seem necessary. Alternative approaches tackling socioecological determinants of ill health are needed for long-term sustainability. Future research could benefit from contributions of non-Western philosophies and perspectives by local researchers.